Simulation-Based Design of Urban Bi-modal Transport Systems - Tilg, Gabriel; Ul Abedin, Zain; Amini, Sasan; Busch, Fritz (Frontiers in Future Transportation, 2020)
The three-dimensional passenger macroscopic fundamental diagram (pMFD) describes therelation of the network accumulation of public transport and private vehicles, and the passengerproduction. It allows for modelling the multi-modal traffic dynamics in urban networks and derivinginnovative performance indicators. This paper integrates this concept into a multi-modal transportsystem design framework formulated as a simulation-based optimization problem. In doing so,we consider the competition for limited road space and the operational characteristics, suchas congestion occurrences, at the strategic design level. We evaluate the proposed frameworkin a case study for the Sioux Falls network. Thereby, we deliver a proof of concept, and showthat the proposed methodology indeed designs a transport system which benefits the overallsystem’s performance. This paper further advances the integration of sequential model-basedoptimization techniques, macroscopic traffic flow concepts, and traffic simulation to design multi-modal transport systems. This supports transport planners and local authorities in composingefficient and robust transport networks.